The Effect of Brand Image, Brand Trust and Price on Repurchase Interest - Hidayatulloh, Fahmi; Susila, Ihwan (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Public transportation and private vehicles are the community's solution for mobilizing all activities. The aim of this research is to analyze the influence of brand image, brand trust and price on interest in repurchasing Vario motorbikes (Study in the Soloraya community of Vario motorbike users). This research method is quantitative. The type of data used in research is primary data. The population in this research is all Soloraya people who use Vario motorbikes. The sample size for this research was 130 respondents. The data analysis technique used in this research is SMARTPLS 3.0 software. This research uses Structural Equation Model (SEM) analysis with Partial Least Square (PLS). The results of this research are that Brand Image has a positive and significant influence on Repurchase Intention. Brand Trust has a positive and significant influence on Repurchase Intention. Price has a positive and significant influence on Repurchase Intention.